Chapter Quantitative explorations of the worldwide distribution of rare characteristics, or the exceptionality of northwestern European languages - Cysouw, Michael (De Gruyter, 2011)
In this article, the distribution of rare features among the world's languages is investigated based on the data from the World Atlas of Language Structures (Haspelmath et al. 2005). A Rarity Index for a language is defined, resulting in a listing of the world's languages by mean rarity. Further, a Group Rarity Index is defined to be able to measure average rarity of genealogical or areal groups. One of the most exceptional geographical areas turns out to be northwestern Europe. A closer investigation of the characteristics that make this area exceptional concludes this article.